Two-dimensional van der Waals heterostructures (vdWHs) with band alignment transformation in multi-functional devices. Issue 48 (2nd November 2022) - Shehzad, Nasir; Saeed, Shahzad; Shahid, Ismail; Khan, Imad; Saeed, Imran; Zapien, Juan Antonio; Zhang, Lixin
Abstract : Two-dimensional van der Waals heterostructures (vdWHs) with tunable band alignment have the potential to be benignant in the development of minimal multi-functional and controllable electronics, but they have received little attention thus far. Abstract : Two-dimensional van der Waals heterostructures (vdWHs) with tunable band alignment have the potential to be benignant in the development of minimal multi-functional and controllable electronics, but they have received little attention thus far. It is crucial to characterize and control the band alignment in semiconducting vdWHs, which determines the electronic and optoelectronic properties. The future success of optoelectronic devices will require improved electronic property control techniques, such as using an external electric field or strain engineering, to change the electronic structures directly. Herein, we review heterostructures fabricated as transition metal dichalcogenides (TMDCs) as one of their constituent monolayers with other notable 2D materials that can transfer from type-II to type-III (type-III > type-II) band alignment when a biaxial strain or electric field is applied.